Dangers of Denying Divine Decree - Ramadhan, Mohammed Bahram (Journal of Islamic Sciences, 2020)
This research aimed to study For a clarifying and Exposing the danger of denying Divine Decree and the miss understanding and invalid thought on this matter, to the limit that some of the riches (kufr) disbelieving in Islam, and explaining the effect of denying fate on religion in aspects of belief, behavior, and acts of worship, As well as exposing the beliefs and ideology of the People of the Sunnah and Group in this matter. is being the method used the descriptive, inductive, critical approach. So that describes the research and shows Dangers of Denying Divine Decree, And trying to guide those who have been afflicted with him, He returned to his senses and his beautiful response with faith By Decree On the approach of the Sunnis and the community. Through my research, I reached the most important results: denying Divine Decree is a slander in Allah’s lordship, his name and attributes and his right to be worship. Negating the decree by most of the people is contradiction because they say: ”Allah didn’t create the evil thing, and they say Allah created the devil and he is the key to all evil”. negating the divine decree contributes to deviating from (sound) behavior and obedience. Negating divine decree obstruction Islamic law order and prohibition. Denying decree will result in lack of belief in a pillar from the 6 pillars of faith, and denying one of the pillars of faith is a major disbelieve that takes the person out of the fold of Islam.